Special Hajj Polemics in Online Media: Quota Scandals, Corruption, and Demands for Transparency - Akhmad Fauzin; Hardi Warsono; Sri Suwitri; Cut Afrina (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2026)
The management of special Hajj quotas in Indonesia has become a subject of public controversy due to concerns over transparency, accountability, and fairness. Allegations of corruption, quota trading, and the diversion of regular Hajj quotas to the special Hajj program have raised questions about the integrity of the existing quota management system. These issues are further aggravated by weak oversight of Special Hajj Organizing Agencies (PIHK) and the absence of an official cap on special Hajj costs, creating opportunities for abuse and unequal access to Hajj services. This study aims to examine the impact of transferring regular Hajj quotas to the special Hajj program on Indonesia’s Hajj management system and to identify policy reforms needed to improve quota governance. Using a qualitative approach with descriptive analysis, the study analyzes online media reports and official documents to identify patterns of quota misuse and evaluate governance practices. The findings reveal significant weaknesses in the transparency and accountability of the special Hajj quota system. Key issues include allegations of corruption involving public officials, special Hajj fees reaching up to IDR 1.1 billion without effective regulation, and the departure of 3,503 pilgrims without undergoing the regular waiting period. The study recommends strengthening transparency in quota allocation, improving regulatory oversight of PIHK, and establishing an official cap on special Hajj costs. These reforms are expected to enhance fairness, accountability, and public trust in Indonesia’s Hajj management system.